Primary leiomyosarcoma of the inferior vena cava necessitating radical resection and reconstruction: case report: Primarni leiomiosarkom spodnje votle vene: prikaz primera z radikalno resekcijo in rekonstrukcijo vene - Hansel, Jan; Mrdža, Božidar; Flis, Vojko (Acta Medico-Biotechnica, 2021)
Primary leiomyosarcoma of the vena cava is a rare tumor. We describe a 63-year-old female in whom a mass was found upon ultrasonographic examination of the abdomen after persistent pain in the right upper quadrant. CT and MRI revealed a malignant intraluminal growth in the inferior vena cava. Radical resec- tion was undertaken to remove the tumor. The inferior vena cava was reconstructed using a PTFE graft. Resection margins were free of tu- mor. Postoperative complications included extended thrombosis below the surgical site and smaller pulmo- nary emboli. A vena-cava filter was inserted to prevent further complica- tions. Twelve months after the first procedure local subcutaneous metas- tases were observed. Metastases were subsequently removed. We discuss our case to deepen our understanding of this extremely rare disease.